INFLUENCE OF DIFFERENT QUALITY OF BUFFALO OOCYTES ON JN - VITRO MATURATION AND FERTILIZATION - SINGH, R P; SHAH, R G; TANK, P H (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 499 freshly collected abattoir ovaries of Surti buffaloes. The total number of different grades of oocytes recovered by slicing method was 1046. The mean numbers of oocytes per ovary of gradeA(2.92 ± 0.14) and B (2.49 ± 0.13) were significantly higher (P<0.05) followed by grade C (1.66 ± 0.09) than that of grade D (1.32 ± 0.10) oocytes, The overall maturation rate achieved for different grades of oocytes was 80.97 per cent in TCM-199 supplemented with 0.6 per cent BSA. The percentage of cytoplasmic maturation observed in oocytesofgradeA, B, C, and D was highest for good (50.30 %), fair (37.70 %) and poor(33.30%)and 28 .60 % ) quality of oocytes, respectively. A significantly higher number of grade A (>3 layer of cumulus cells) and grade B (1-3 layer of cumulus cells) quality of oocytes attained good cytoplasmic maturation than grade C (less compact cumulus cells) and grade D (nude oocytes). The total maturation rate from gradeAoocytes was highest (87.94 %) followed by oocytes of grade B (82.91 %) and grade C (72.22 %). The nuclear maturation was evaluated in 528 oocytes by Hoechst 33342 stain. The highest number of gradeAoocytes (26.00 %) reached to M-ll stage, followed by grade B (24.21 %) and grade C (14.28 %) and none of the oocytes from grade D reached to M-11 stage; they were mainly arrested at GV and GVBD stage. Oocytes of grade A (n=181) and B (n::::305), which had cytoplasmic maturation, were utilized for in-vitro fertilization. The overall fertilization rate observed was 20.16 per cent for grade A and B oocytes. The higher fertilization rate was observed for grade A(21.00 % ) oocytes than that in grade B (19.67 %). The study revealed that the presence of cumulus layer around the oocytes affected the maturation and fertilization rate of buffalo oocytes. Significantly (P<O .05) greater number of oocytes per ovary was recovered (3.31 ± 0.36) when the CL was absent compared with ovaries on which CL was present 1.01 ± 0.05). Thus, the effect of presence Vs absence of CL on the ovaries had significant effect on recovery rate of buffalo· oocyte.